A Novel Hybrid Conceptual MCDM Model to Assess and RankThe ‎Performance of Cold Storage Service Providers - Gurrala , Prof. Kavitha Reddy; Gonela , Dr. Saradhi (International Journal of Accounting and Economics Studies, 2025)
Cold Chains (CCs) furnish a regulated environment for the storage, transportation, and ‎distribution of temperature sensitive products. Cold Storage Service Providers (CSSPs) act as ‎intermediaries within the food processing value chain by preserving the quality of a wide ‎range of foods. Further, Cold Chain Performance (CCP) is crucial towards maintaining ‎quality, safety, and economic value of the foods. Consequently, several research studies ‎focused on formulating Multi-Criteria Decision-Making (MCDM) models to enhance CCP. ‎Nevertheless, the focus of such studies was on enhancing performance within specific ‎dimensions viz., sustainability, traceability, digitalization, or resilience etc. Accordingly, this ‎study aims at addressing the research gap, by formulating a novel hybrid conceptual MCDM ‎model integrating Fuzzy Analytical Network Process (FANP) and MultiAtributive Ideal-Real ‎Comparative Analysis (MAIRCA) to holistically assess and rank the performance of CSSPs ‎across multiple performance dimensions.